Accountability in Healthcare: Sovereign Authority to Democratization. Issue 3 (March 2023) - Nakayama, Don K.
While accountability in healthcare is associated with Ernest Amory Codman (1869-1940), its origins can be traced to the beginning of recorded history. A physician guilty of a medical misdeed under the Code of Hammurabi (ca. 1755 BCE) had his fingers severed. The authority to regulate medical practice passed from sovereign to physicians in 1241 when emperor Frederick II gave the medical faculty of the University of Salerno the responsibility of examination and licensure to practice medicine. Thomas Linacre (1460-1524) convinced Henry VIII to assign licensure to a newly constituted College of Physicians (1518) that set standards for education and practice. In his code of medical ethics (1803) Thomas Percival (1740-1804) introduced the notion that medical misdeeds be judged by a panel of peers. In enacting an analogous code (1847) the American Medical Association incited strong opposition from a prevailing attitude of professional autonomy distrustful of outside interference (1883). Codman's innovation, the End Result system (1914), reflected his belief that surgery was an industrial process where the goal was perfection: survival without complications and full recovery to complete health. This required the systematic collection of clinical data on all surgical patients and an objective assessment of outcome. The approach evolved decades later to modern concepts of quality improvement (QI), using scientifically derived data to standardize processes and minimize variability and sources of error. With the objective tools of QI physicians and their patients judge for themselves the care they offer and select under the democratization of healthcare.